Blue luminescent N, S-doped carbon dots encapsulated in red emissive Eu-MOF to form dually emissive composite for reversible anti-counterfeit ink. Issue 5 (14th January 2021) - Gao, Jin-Ping; Yao, Ru-Xin; Chen, Xiao-Hui; Li, Hui-Hui; Zhang, Chao; Zhang, Fu-Qiang; Zhang, Xian-Ming
Abstract : By suitable combination a Eu-MOF and its dual-emission fluorescence composite N, S-CDs@Eu-MOF, a visible fluorescent probe for detecting water content in organic solvents and a reversible anti-counterfeit ink were established. Abstract : Lanthanide metal–organic frameworks (Ln-MOFs) have demonstrated great potential in luminescence sensing and optical anti-counterfeiting. High-security anti-counterfeiting technology is of great importance and requires the development of universal luminescent materials with multiple modes of emission and adjustable photoluminescence. Herein, a 3D red light emission microporous europium(iii ) metal–organic framework [Eu3 (OH)(1, 3-db)2 (H2 O)4 ]·3H2 O (1 ) (1, 3-db = 1, 3-di(3′, 5′-dicarboxylpheny) benzene) was constructed from a zigzag [Eu3 (COO)8 ] chain and π-electron-rich terphenyl-tetracarboxylate. Notably, the quenched fluorescence of 1 under hydrogen chloride vapor could be recovered upon fuming by a vapor of Et3 N. Most strikingly, the strong blue light emission by nitrogen and sulfur co-doped carbon dots (N, S-CDs) could be encapsulated in 1 to generate a dual-emission composite, namely, N, S-CDs@Eu-MOF, which shows solvent-dependent photoluminescence: N, S-CD-related blue luminescence in water and Eu-MOF-related red emission in organic solvents. Taking advantage of the above unique reversible fluorescent behavior, Eu-MOF and N, S-CDs@Eu-MOF are prepared as fluorescent high-security inks to achieve data encryption and decryption on specific flower patterns.